Education in a Global Age: An Inter-California Strategy for the Tijuana-San Diego Region - Vásquez, Olga A. (Frontera Norte, 2017)
This article lays out a blueprint for an Inter-California Strategy that would link the San Diego and Tijuana areas as one regional force. It attempts to conceptualize two distinct and often disharmonious areas as one, painting with broad strokes the uneven economic and educational conditions on the two sides of the border. It discusses past binational collaboration on education and sketches the possibilities for future collaboration, offering timely recommendations to bring it about and predictions for what it could achieve. In calling for an inter-California region, the article also argues for a global identity and, specifically, for an education that is relevant to the new economic, technical, and scientific advances that are increasingly illuminating a new global society. RESUMEN Este artículo presenta un bosquejo para una estrategia Inter-California que enlazaría las áreas de San Diego y Tijuana como una sola fuerza regional. Esto intenta conceptualizar dos distintas y frecuentemente contradictorias áreas como una sola, haciendo una aproximación grosso modo de las desiguales condiciones económicas y educativas en ambos lados de la frontera. Se discute la colaboración binacional en educación, del pasado y se plantean las posibilidades para el futuro de dichacolaboración, ofreciendo recomendaciones y predicciones de las metas que podrían alcanzarse. Llamando a la región inter-California, el artículo también argumenta por una identidad global, y específicamente, por una educación que es relevante para la nueva economía, así como los avances científicos y tecnológicos que están iluminando cada vez más una nueva sociedad global.